THE EVIL: THE FRAGILITY OF THE KANTIAN MORALITY AGAINST A PROPENSION - Isaza, Jhon Alexander (Disertaciones, 2019)
The First, in Blind love as an evil of the body , I will show you fragments of two letters (one sent to Immanuel Kant by one of his readers, moved by a passional and moral anguish, by a lack of love, the next from one friend to another, both readers of Kant, and one of them in particular disagreement with one of his theses), both will serve as an excuse to introduce the idea that will develop in the text: the forms of evil in man, and what, according to Kant, we had to do before them. In the second part, What is radical evil , I will present Kant's best-known thesis on the idea of evil, and I will offer a kind of glossary divided into five points that we can take as a basis for understanding the thesis, and to move on to the third part, which is, in turn, the philosophical point of the beginning of the exhibition, Why evil is a problem for Kant: this part will present what is the problem of evil, and indicate what could mean a solution to it. Part four will force us to ask a question that will be answered in part five: Who is responsible for solving the problem of evil. Once presented seven additional characteristics of the Kantian evil, which will lead us to the answer: it is the rational religion that is responsible for solving the problem of evil. In the fifth part, Metaphy sics: from the postulates of practical reason to rational religion, it will be shown what alternative is left to natural religion against evil and how it relates to it, which will finally lead us to contemplate amazement the fragility of the Kantian moral world against evil.
Keywords: Immanuel Kant; moral; evil; good; free will; rational religion